Study of Ordering in Fe—25%Al—Cr Alloys by Dilatometry, Heat Flow and Mechanical Spectroscopy - Belamri, Z.; Hamana, D.; Golovin, I.S.; Chudakov, I.B. (Металлофизика и новейшие технологии, 2013)
It is known that the addition of Cr to the Fe₃Al-based alloys leads to an improvement in their ductility and other properties. In a given work, dilatometric, differential scanning calorimetric (DSC) and internal friction tests are performed to study the ordering process in stoichiometric and overstoichiometric Fe₃Al alloys with Cr addition at a constant heating rate from room temperature up to 1000°C. The results indicate that the addition of Cr slows the D0₃-type ordering process; this can be confirmed by obtained values of activation energy. Cr addition has also an effect on the mechanical properties of studied alloys annealed in D0₃-type order domain. The heights and broadening of three peaks (of X-, Zener-, and Snoek-type) can be changed at the presence of Cr. X-ray diffraction (XRD) and TEM studies are carried out at different temperatures chosen from the obtained DSC curves and affirmed that a rapid quenching just after heat treatment from highest temperature cannot suppress the formation of B2 ordered particles in overstoichiometric Fe₃Al alloys. Відомо, що додавання Cr до стопів на основі Fe₃Al спричиняє поліпшення їх пластичности та інших властивостей. У даній статті виконано дилатометричні випробування та випробування методами диференційної сканівної калориметрії (ДСК) і внутрішнього тертя з метою вивчення процесу впорядкування в стехіометричних та надстехіометричних стопах Fe₃Al з додаванням Cr при сталій швидкості нагрівання від кімнатної температури до 1000°C. Додавання Cr сповільнює процес упорядкування за надструктурним типом D0₃, що підтверджується одержаними значеннями енергії активації. Додавання хрому впливає також на механічні властивості досліджених стопів, відпалених в області D0₃-порядку. Висоти та розширення трьох піків (Зінерового, Снукового та X-типу) можуть змінюватися в присутності Cr. Рентґенодифракційна аналіза та трансмісійна електронна мікроскопія, виконані за різних температур, обраних на підставі одержаних ДСК-кривих, підтвердили, що швидке гартування від самої високої температури зразу після теплового оброблення не може пригнітити формування впорядкованих частинок типу B2 у надстехіометричних стопах Fe₃Al. Известно, что добавление Cr к сплавам на основе Fe₃Al приводит к улучшению их пластичности и других свойств. В данной статье выполнены дилатометрические испытания и испытания методами дифференциальной сканирующей калориметрии (ДСК) и внутреннего трения с целью изучения процесса упорядочения в стехиометрических и сверхстехиометрических сплавах Fe₃Al с добавлением Cr при постоянной скорости нагрева от комнатной температуры до 1000°C. Добавление Cr замедляет процесс упорядочения по сверхструктурному типу D0₃, что подтверждается полученными значениями энергии активации. Добавление хрома влияет также на механические свойства исследуемых сплавов, отжигаемых в области D0₃-порядка. Высоты и уширение трёх пиков (зинеровского, снуковского и X-типа) могут изменяться в присутствии Cr. Рентгенодифракционный анализ и просвечивающая электронная микроскопия, выполненные при различных температурах, выбранных на основании полученных ДСК-кривых, подтвердили, что быстрая закалка от самой высокой температуры сразу после тепловой обработки не может подавить формирование упорядоченных частиц типа B2 в сверхстехиометрических сплавах Fe₃Al.